Lower Lip Paresthesia in a Patient With Carious Mandibular Premolar: A Case Report - Hira Butt; Maria Jabbar; Sadaf Amjad Khawaja (Gandhara University, 2023)
Several dental operations, including local anaesthetic administrations, wisdom teeth procedures, orthognathic surgical treatments, ablative operations, implantation, and root canal therapy, can cause numbness and tingling of the inferior alveolar nerve. The present case report explains a case report of lower lip paresthesia arising due to carious mandibular premolar.